Lifetime indirect cost of childhood overweight and obesity: a decision analytic model - Sonntag, Diana; Ali, Shehzad; Bock, Freia de (Obesity, 2016)
Objective To estimate the indirect lifetime cost of childhood overweight and obesity for Germany. Methods The lifetime cohort model consisted of two parts: (a) Model I used data from the German Interview and Examination Survey for Children on prevalence of BMI categories during childhood to evaluate BMI trajectories before the age of 18; and (b) Model II estimated lifetime excess indirect cost based on the history of childhood BMI. Indirect costs were defined as the opportunity cost of lost productivity due to mortality and morbidity and were identified through a systematic literature review. Results Our analysis showed that the majority of children with overweight and obesity remained in the same BMI category during their adult life, resulting in significant indirect lifetime costs. We estimated that overweight and obesity during childhood resulted in an excess lifetime cost per person of €4,209 (men) and €2,445 (women). For the current prevalent German population, the excess lifetime cost was €145 billion. Conclusions Our study showed that childhood obesity results in significant economic burden on the society. Therefore, cost-effective strategies targeted at reducing the prevalence of obesity during the early years of life can significantly reduce both healthcare and nonhealthcare costs over the lifetime.
Gesehen am 12.02.2019
Published online 6 December 2015